Analisis Hukum Terhadap Perlindungan Hak Mayarakat Adat Pubabu – Besipae Atas Tanah Ulayat dan Hutan Adat di Wilayah Nusa Tenggara Timur - Praswandho, Efhardian; Prihadiati, RR. Lyia Aina (FOCUS, 2025)
The conflict between the Pubabu-Besipae Indigenous Community in East Nusa Tenggara and the provincial government reflects the complexity of the lack of recognition and protection of the Pubabu-Besipae Indigenous Community's rights to customary land and forest. Article 18B Paragraph (2) of the 1945 Constitution and various regulations have provided the legal basis for such recognition. However, implementation still faces obstacles, including the lack of government support for the recognition and protection of the Pubabu-Besipae Indigenous Peoples, including their rights related to customary land and forest. This research analyses the legal protections needed to ensure the Pubabu-Besipae indigenous community's right to recognition and protection as an indigenous community and to protect the right to customary land and customary forest to be managed by the Pubabu-Besipae indigenous community in a sustainable manner.